Novel Insights into Amlodipine-Induced Gingival Enlargement: A Clinical and Molecular Perspective - Jana Mojsilović; Nemanja Jovičić; Sanja Vujović Ristić; Momir Stevanović; Sara Mijailović; Gvozden Rosić; Slobodan Janković; Marina Kostić (MDPI AG, 2024)
This study aimed to identify risk factors for amlodipine-induced gingival enlargement, assess quality of life, and analyze gingival tissue. This cross-sectional study involved hypertensive patients on amlodipine, divided into groups with and without gingival enlargement. Assessments included sociodemographic data, clinical evaluations, and clinical parameters. Quality of life was assessed using OHIP-14 and WB-HRQoL scales. Gingival tissue samples were analyzed for oxidative status and key molecules using RT-PCR and colorimetric assays. The study included 32 patients with no significant sociodemographic differences between groups (p > 0.05). Patients with gingival enlargement had higher systolic blood pressure (139.63 ± 10.743 vs. 128.38 ± 7.249, p = 0.028) and higher OHIP-14 scores. The RT-PCR analysis showed significant differences in IL-6, TNF-α, IL-33, ST2, TGF-β1, FGF-2, CTGF, VEGF-D, and KGF expression. IL-6, TNF-α, ST2, and FGF-2 expression levels were lower in patients taking amlodipine, with and without gingival enlargement. TGF-β1 and CTGF expression levels were highest in patients with amlodipine-induced gingival enlargement. SOD activity was also highest in these patients, whereas MDA levels were higher in patients with gingival enlargement without amlodipine. Our study highlights the impact of amlodipine-induced gingival enlargement on oral health and quality of life, emphasizing fibrosis and oxidative stress, and suggests the need for integrated healthcare approaches and further research.